What patients want from the treatment of Dupuytren's disease — is the Unité Rhumatologique des Affections de la Main (URAM) scale relevant?. (February 2015) - Rodrigues, J. N.; Zhang, W.; Scammell, B. E.; Davis, T. R. C.
Patients awaiting surgery for Dupuytren's contractures listed the problems from their Dupuytren's disease that had led them to request surgery and their relative priorities of the results of surgery. The listed problems were compared with the nine items comprising the Unité Rhumatologique des Affections de la Main (URAM) Dupuytren's disease-specific outcome measure. One hundred and ten patients reported 278 problems. Ninety-four different combinations of problems were provided by patients, and over half (55%) of the problems were not captured by items in the URAM scale. The long-term outcome from surgery was relatively more important to patients than speed of recovery. The URAM tool may not be relevant to patients in the UK, and further assessment of its face validity is required before it is used. Level of evidence: III